J Psychol Psychother 2019
DOI: 10.35248/2161-0487.19.9.355
|View full text |Cite
|
Sign up to set email alerts
|

Indigenous Counseling System of Oromo Community in Ethiopia

Abstract: Even though the concept of counseling in the modern society and indigenous community vary vibrantly, the purpose of counseling is the same globally. Counseling is a serving approach for individuals 'within the system'. Oromo as a larger community in Ethiopia, Africa, has its own wisdom and way of living which is not studied well. Accordingly, this study was intended to analyze the efficacy of indigenous counseling approaches ever practiced among Oromo community. Five districts/zones/employing indigenous counse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Prevention counselling involving reconciliation, conflict resolution and peacekeeping (maintaining peace and stability) is the most essential philosophy of elder counsellors' life routines. Consistent with this, Abeshu & Baissa (2019) indicated that indigenous counselling is characterised by a preventive approach to stabilise and maintain peace and security among the local citizens. It is exceedingly effective in minimising the risk of behavioural, emotional, social, political and economic challenges before they emerge.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Prevention counselling involving reconciliation, conflict resolution and peacekeeping (maintaining peace and stability) is the most essential philosophy of elder counsellors' life routines. Consistent with this, Abeshu & Baissa (2019) indicated that indigenous counselling is characterised by a preventive approach to stabilise and maintain peace and security among the local citizens. It is exceedingly effective in minimising the risk of behavioural, emotional, social, political and economic challenges before they emerge.…”
Section: Discussionmentioning
confidence: 88%
“…This issue is entertained under reconciliation, which might take days of discussion and may require the involvement of counsellors at different levels. Abeshu & Baissa (2019) discussed the three levels of counselling at family, kinfolk and elder counsellor levels, which work effectively in the community milieu to facilitate counselling and reconciliation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sedulur Samin Kudus has done it. This is done in the Oromia community where they carry out counseling with traditional elders to teach, guide, and reconcile (Abeshu & Baissa, 2019). As expressed by Lau (Lau, 2000), providing counseling with the same background between the counselor and the counselee will accept the advice from the counselor.…”
Section: Indigenous and Exogenous In The Samin Kudus Communitymentioning
confidence: 99%
“…They prefer psychotherapy therapists who are relatively similar in attitude, personality, ethnicity, and gender. In indigenous peoples, (Abeshu & Baissa, 2019) researching the people of Oromia, Ethiopia. They have elders as community leaders, and religious and ritual leaders, who are involved in advising the team to teach, guide, reconcile, and conduct counseling in the community.…”
Section: Introductionmentioning
confidence: 99%